2023
DOI: 10.1002/adfm.202306170
|View full text |Cite
|
Sign up to set email alerts
|

Introducing MR‐TADF Emitters into Light‐Emitting Electrochemical Cells for Narrowband and Efficient Emission

Shi Tang,
John Marques dos Santos,
Joan Ràfols‐Ribé
et al.

Abstract: Organic semiconductors that emit by the process of multi‐resonance thermally activated delayed fluorescence (MR‐TADF) can deliver narrowband and efficient electroluminescence while being processable from solvents and metal‐free. This renders them attractive for use as the emitter in sustainable light‐emitting electrochemical cells (LECs), but so far reports of narrowband and efficient MR‐TADF emission from LEC devices are absent. Here, this issue is addressed through careful and systematic material selection a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
0
0
Order By: Relevance
“…The significantly improved operational stability of the TPA-tBu-DiKTa LECs can be attributed to the shorter value of τ d (Table 1), which will mitigate both exciton-exciton and exciton-polaron quenching and related deleterious side reactions. In this context, we mention that the measured operational lifetime of the optimized TPA-tBu-DiKTa LEC represents an improvement by a factor of 5 compared to the state-of-the-art [33] in the MR-TADF LEC field.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The significantly improved operational stability of the TPA-tBu-DiKTa LECs can be attributed to the shorter value of τ d (Table 1), which will mitigate both exciton-exciton and exciton-polaron quenching and related deleterious side reactions. In this context, we mention that the measured operational lifetime of the optimized TPA-tBu-DiKTa LEC represents an improvement by a factor of 5 compared to the state-of-the-art [33] in the MR-TADF LEC field.…”
Section: Discussionmentioning
confidence: 98%
“…[53,54] This opportunity for material-and energy-efficient fabrication is desirable for cost-sensitive and sustainable electroluminescent devices, but it should be noted that the LEC performance is strongly dependent on the merits and combined function of the luminescent semiconductor and the mobile ions. For instance, it has recently been demonstrated that MR-TADF compounds can function as the luminescent organic semiconductor in LEC devices, [4,22,32,33] but also that the propensity for ACQ can be highly detrimental to both the LEC-critical ion redistribution process and the emission efficiency. [45] It is thus interesting and timely to investigate and compare the performance of LECs employing TPA-tBu-DiKTa and TPPO-tBu-DiKTa.…”
Section: Light-emitting Electrochemical Cellsmentioning
confidence: 99%
See 1 more Smart Citation